A NAVARASA BASED LYRICAL ANALYSIS OF SONGS FROM THE MOVIE ANIMAL - Sailaxmy, R.; Prabakaran V. (ShodhKosh: Journal of Visual and Performing Arts, 2025)
There are numerous forms of music in this world and film music is something that is special to Indian Cinema. Be it the background score or the songs, Indian Cinema is known for weaving in music into the script. The primary components of a good album are catchy music and relatable lyrics. Intertwining these songs into the story in order to enhance a scene’s emotional connect is not new to Bollywood. Music along with appropriate lyrics project the emotions on screen and draw the audience closer to the feelings of the characters. Lyrics are the soul of a song. They are raw feelings that flow through tunes and give us a sense of connectivity even if there are no visuals. In this paper, we would like to study the lyrics from the music of a recent Bollywood movie “Animal” through the perspective of Navarasa - an ancient Indian Aesthetic theory. The main objective is to analyze how lyrical elements contribute to the evocation of specific rasas/ emotion and to examine the emotional alignment between the song lyrics and the narrative context of the film.